A comparison of visual analog scale and categorical ratings of headache pain in a randomized controlled clinical trial with migraine patients - Lines, Christopher R; Vandormael, Kristel; Malbecq, William (Pain (Amsterdam), 2001)
A visual analog scale (VAS) method of assessing headache pain was compared with a standard categorical four-grade scale (4GS) in a randomized, placebo-controlled, double-blind, clinical trial involving 792 treated migraine outpatients who received oral rizatriptan 5 mg, sumatriptan 50 mg, or placebo for a moderate or severe headache. The VAS and 4GS were equally useful in demonstrating that the active drugs were superior to placebo at reducing headache pain, and in showing that the active drugs were similarly effective. For both rizatriptan and sumatriptan, slightly larger effect sizes were observed with the 4GS compared with the VAS. In analyses using data combined across all treatment groups, VAS and 4GS scores were highly correlated. Use of the VAS imposed additional administrative burdens. These findings suggest that the 4GS may be the preferred scale for assessing headache pain in clinical trials involving adult migraineurs.